Statistical Approach to Study the Ambient Air Quality Parameters in Bileipada, Keonjhar, Odisha, India - Kumar Dash, Suvendu; Kishore Dash, Aditya; Pradhan, Avanti (International Journal of Engineering and Technology, 2018)
Monitoring and assessment of ambient air quality within a definite interval of time is the only way to find out the existing atmospheric conditions and the source of emissions. The monitoring of different parameters such as PM10, PM2.5, SO2 and NO2 were carried out for a period of three years covering all seasons starting from March, 2013 to Feb’ 2016. The total collection and monitoring methods were executed as per the standard methods of CPCB. For better analysis one-way and two-way analysis of variance (ANOVA) test has been applied to different monitored results based on different monitoring stations and seasons. In two-way ANOVA test for stations, the F values computed as 34.028, 35.362, 34.113 and 29.090 for PM10, PM2.5, SO2 and NO2 respectively are found to be highly significant (at P<0.01). Further due to variations in seasons the F were values computed to be 280.290 (PM10), 225.626 (PM2.5), 306.569 (SO2) and 100.281 (NO2) which indicate that there is a significant variation in different parameters. This study can provide a platform to new researcher in the field of air quality monitoring in other areas.